Big enough = Bastante grande - Lachtman, Ofelia Dumas; Sanchez, Enrique O., 1942-; Canetti, Yanitzia, 1967- (Houston, Tex. : Pinata Books, 1998)
When a treasured piñata is threatened, little Lupita discovers that she is big enough to help her mother.
Accelerated Reader
Keywords: Size judgment -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Pinatas -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Theft -- Juvenile fiction; Spanish language materials -- Bilingual -- Juvenile literature; Tamano -- Novela juvenil; Madre e hija -- Novela juvenil; Mexicano-americanos -- Novela juvenil; Robo -- Novela juvenil; Materiales bilingues en espanol -- Literatura juvenil; Pinatas -- Novela juvenil